Bis-Histidyl adducts in tetrameric hemoglobins - VERGARA, ALESSANDRO; MAZZARELLA, LELIO; G. di Prisco; C. Verde (Springer, 2008)
In the last decade crystallographic evidence for endogenous coordination at the sixth coordination site of the heme iron has been reported for monomeric haemoglobins (Hbs) in both the ferrous (haemochrome) and ferric (haemichrome) oxidation state. Usually, the sixth ligand is provided by the imidazole side chain of a His, the only putative ligand normally present in the distal site of the heme pocket. More recently, structural and spectroscopic evidence has been reported, which show that the bis-histidyl adduct in the ferric state represents a common accessible ordered state also for several tetrameric Hbs isolated from Antarctic fish, both in the solid and solution state. Bis-histidyl coordination was also discovered in the crystals of horse met-Hb exposed to acidic pH. All these crystal structures are characterised by a different binding state of α and β chains. Tetrameric Hbs with all chains in the bis-histidyl coordination state have not yet been found. Herein we review the structural details of the recent results in this field, together with solution studies on the pathway of haemichrome formation